DEPICTING STEREOTYPICAL REPRESENTATION OF FEMALE CHARACTER IN ANTON CHEKHOV'S LADY WITH THE DOG' - Athriyana S. Pattiwael (Universitas Bandar Lampung, 2019)
Writers reside in particular time and place would portray their surrounding socio-cultural context through their literary works. Yet, they may also use their works to articulate their concerns and critics upon particular socio-cultural practices. Literary works then is ideological. Utilizing Critical Discourse Analysis as the approach and Transitivity as the analytical tool, this study then focuses on uncovering representation of female character in a selected short story by Anton Chekhov. Representation here is perceived as discursive practice in which patriarchy is considered to be the working ideology. The results show that female character is represented stereotypically and gender-biased in what she does, what she says, what she thinks and what she feels. The result also suggests that the practice of dual representation and ambivalence is also evident in female character representation.